A Phytochemical Analysis of Kigelia pinnata - Jain, P.S.; Belsare, D.P.; Pal, S.C.; Mandal, S.C. (Asian Journal of Chemistry, 2010)
The stem bark part of the plant, Kigelia pinnata, was analyzed phytochemically and a compound was isolated from the petroleum ether extract. The compound was characterized, employing chemical and spectral methods, and found to be a β-sitosterol.